Measuring labour differences between natives, non-natives, and natives with an ethnic-minority background - Nick Drydakis (Global Labor Organization (GLO), 2017)
Through a field study we measure differences in employment outcomes between natives, non-natives, and natives with an ethnic-minority background. It is suggested that the joint effect of productivity uncertainties and distastes against ethnic-minority groups should be higher for non-natives than for natives with an ethnic-minority background. However, it is revealed that both non-natives and natives with an ethnic-minority background face comparable occupational access constraints and are sorted into similarly lower paid vacancies. An ethnic name regardless of one's nationality is enough to generate unequal treatments.
Keywords: J15; J31; J71; 330; Occupational access; Wages; Ethnic Minorities; Discrimination